Sensitization to airborne and food allergens in Reykjavík (Iceland) and Uppsala (Sweden) - a comparative study. - Gislason, D; Bjornsson, E; Gislason, T; Janson, C; Sjöberg, O; Elfman, L; Boman, G (Allergy, 2009)
To access publisher full text version of this article. Please click on the hyperlink in Additional Links field BACKGROUND: The aim of this study was to compare the prevalence of atopic sensitization and possible risk factors for allergies in two ethnically similar but geographically widely separated urban populations. METHODS: Data from two centers of the European Community Respiratory Health Survey, Reykjavik, Iceland, and Uppsala, Sweden, were utilized. This included a structured interview, skin prick tests, and blood samples for total and specific IgE for common aeroallergens. Additional measurements of specific IgE antibodies to common food antigens were performed. Furthermore, data on social environment, lifestyle, air pollution, and meteorologic variables were compared. RESULTS: Skin prick tests were done on 540 individuals in Reykjavik and 527 in Uppsala. The overall prevalence of at least one positive prick test was 20.5% in Reykjavik and 34.2% in Uppsala (P<0.001). Total and specific IgE were measured in serum from 521 subjects in Reykjavik and 472 in Uppsala. The geometric mean value for total IgE was significantly lower in Reykjavik (13.4 kU/l) than in Uppsala (24.7 kU/l) (P<0.001). Similarly, the overall prevalence of at least one specific IgE to airborne allergens was 23.6% in Reykjavik and 32.3% in Uppsala (P<0.01). Specific IgE to a food panel (fx5) was measured in 502 subjects in Reykjavik, and 434 in Uppsala. In Reykjavik, 20 individuals (4.0%) were positive to one or more of the allergens in the food panel compared to 27 (6.0%) in Uppsala. When the single allergens present in the food panel were measured, altogether 16 positive reactions were found in Reykjavik compared to 47 in Uppsala (P<0.05). CONCLUSIONS: The prevalence of sensitization to both airborne and food allergens was lower in Reykjavik than in Uppsala. The difference may be due to environmental and/or dietary differences or to some yet undefined factor.